DETERMINANTS OF PROFESSIONAL MOTIVATION OF SOCIAL WORKERS WORKING WITH PEOPLE WITH DISABILITIES - Bubnys, Remigijus; Milašiūtė, Eglė (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The main precondition for good care of people with disabilities is not only social workers’ knowledge of pedagogical, psychological or social work but also their own personal qualities, values, attitudes, empathy and psychological resilience in difficult situations. Professional motivation encompasses employees’ motives and needs guiding them to purposefully certain personal and organisational goals. Motivation is the basis and the cause of the professional activity, which is related to the satisfaction of the employee's needs and which may be conditioned by the employee's experience. Problems of the research: What are the intrinsic and extrinsic factors of social worker’s motivation to work? The aim is to analyse the motivation factors of professional activities of social workers working with people with disabilities. Research methods: 1) A semi-structured interview for data collection; 2) A qualitative content analysis based on the content of the analysed text. Sample. The survey involved 12 social workers from Lithuania who work with with people having disabilities. The results disclose intrinsic and extrinsic factors of social workers’ professional motivation in Lithuania. Extrinsic factors that stimulate social workers are not the main source of motivation for work. Social workers point out that the main factors driving employees to work are the pay, working conditions and work environment, well-being in the work environment, positive feedback from the manager, co-workers’ support and trust, client appreciation, manager praise. Intrinsic factors promoting social workers' professional activities are self-realization, opportunities for improvement, clients’ well-being, training in supervision, qualification improvement.